The economics of central bank digital currency - Toni Ahnert; Katrin Assenmacher-Wesche; Peter Hoffmann; Agnese Leonello; Cyril Monnet; Davide Porcellacchia (European Central Bank (ECB), 2022)
This paper provides a structured overview of the burgeoning literature on the economics of CBDC. We document the economic forces that shape the rise of digital money and review motives for the issuance of CBDC. We then study the implications for the financial system and discuss of a number of policy issues and challenges. While the academic literature broadly echoes policy makers' concerns about bank disintermediation and financial stability risks, it also provides conditions under which such adverse effects may not materialize. We also point to several knowledge gaps that merit further work, including data privacy and the study of end-user preferences for attributes of digital payment methods.
Keywords: E41; E42; E51; E52; E58; G21; 330; Central Bank Digital Currency; Digital Money; Payments; Monetary Policy; Financial Stability